Anisotropic g factors of the tetragonal Cu²⁺ monomer in Tl-2223 superconductor - Zhi-Hong Zhang; Shao-Yi Wu; Min-Quan Kuang; Chang-Chun Ding (Физика низких температур, 2015)
The gyromagnetic factors of the Cu²⁺ monomer in Tl-2223 superconductor are quantitatively investigated from the perturbation formulas of these factors for a 3d⁹ ion in a tetragonally elongated octahedron. The local tetragonal distortion of the system is attributable to the axial elongation along c axis, corresponding to the five-fold coordinated Cu²⁺(2) site with almost 30% longer Cu–O bond length for the apical oxygen as compared to the four planar ones. The significant anisotropic behaviors of the EPR spectra perpendicular to and parallel with the ab (CuO₂) layers are analyzed on the basis of the local tetragonal elongation.